Epicardial fat volume, an independent risk factor for major adverse cardiovascular events, had an incremental prognostic value to myocardial perfusion imaging in Chinese populations with suspected or known coronary artery disease with a normal left ventricular ejection fraction - Yang, Le; Yu, Wenji; Wan, Peng; Wang, JingWen; Shao, Xiaoliang; Zhang, Feifei; Yang, Xiaoyu; Chen, Yongjun; Li, Qi; Jiang, Dan; Wang, Yufeng; Jiang, Qi; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background. A large number of coronary artery disease (CAD) patients with normal left ventricular ejection fraction (LVEF) had poor prognosis. As a routine examination, SPECT-MPI is useful for risk stratification and predicting the occurrence of major adverse cardiovascular events (MACE) in suspected or known CAD populations. SPECT/CT is an "one-stop shop" examination, which through non-contrast CT can product attenuation correction for MPI and obtain information of coronary artery calcium (CAC) and epicardial fat volume (EFV) simultaneously. This study aimed to investigate the predictive and incremental value of EFV to MPI for MACE in Chinese suspected or known CAD populations with normal LVEF. Methods. and Results. We retrospectively studied 290 suspected or known CAD inpatients with normal LVEF who underwent SPECT/CT from February 2014 to December 2017. Abnormal MPI was defined as SSS ≥ 4 or SDS ≥ 2. EFV and CAC was calculated by non-contrast CT. The end of follow-up was February 2022. MACE was defined as cardiac death, late coronary revascularization ≥ 3 months after MPI, nonfatal myocardial infarction, angina-related rehospitalization, heart failure, and stroke. During the 76-month follow-up, the event-rate was 32.0% (93/290). Univariate and multivariate Cox regression analysis concluded that high EFV (>108.3 cm 3 ) (HR: 3.3, 95% CI: 2.1, 5.2 P<0.000) and abnormal MPI (HR: 1.8, 95% CI: 1.1, 2.8 P=0.010) were independent risk factors of MACE. The 3 event-free survival of patients with high EFV was significantly lower than low EFV group (log-rank test P<0.001). In the subgroup with normal MPI, high EFV was associated with reduced event free survival (log-rank P<0.01), with higher annualized event rate (8.3% vs 1.9%). Addition of high EFV to MPI could predict MACEs more effectively, with larger concordance index (0.56 to 0.69, P<0.01)，higher Global chi-square (7.2 to 41.4, P<0.01), positive IDI (0.10, P<0.01) and NRI (0.37, P<0.01).In Chinese suspected or known CAD populations with normal LVEF, high EFV was an independent risk factor for MACE after adjusting for traditional risk factors, CAC and MPI. In subgroups with normal MPI, EFV could also improve risk stratification. Addition of EFV to MPI had incremental value for predicting MACE.